A Facile Microwave Hydrothermal Method for Fabricating SnO2@C/Graphene Composite With Enhanced Lithium Ion Storage Properties - Liu, Li-Lai; Li, Ming-Yang; Sun, Yi-Han; Yang, Xue-Ying; Ma, Min-Xuan; Wang, Hui; An, Mao-Zhong (Frontiers in Chemistry, 2022)
SnO2@C/graphene ternary composite material has been prepared via a double layer modified strategy of carbon layer and graphene sheets. The size, dispersity and coating layer of SnO2@C are uniform. The SnO2@C/graphene has a typical porous structure. The electrochemical performances of SnO2@C/graphene are better than those of carbon spheres/graphene in lithium-ion batteries, SnO2@C and SnO2/graphene according to the results of comparative experiments. The first lithium insertion and lithium extraction capacities of SnO2@C/graphene are 2210 and 1285 mAh·g-1 at a current density of 1000 mA·g-1, respectively. The coulombic efficiency is 58.60%. The reversible specific capacity of SnO2@C/graphene anode is 955 mAh·g-1 after 300 cycles. The reversible specific capacity still maintains an average of mAh·g-1 even at the high current density of 5 A·g-1. In addition, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) are performed to further investigate the SnO2@C/graphene composite material prepared by microwave hydrothermal method. As a result, SnO2@C/graphene has demonstrated a better electrochemical performance.